Quantitative determination of estrogen receptor, progesterone receptor, and HER2 mRNA in formalin-fixed paraffin-embedded tissue: a new option for predictive biomarker assessment in breast cancer - Pfitzner, Berit Maria; Kronenwett, Ralf; Hennig, Guido; Euting, Heike; Weber, Karsten; Bohmann, Kerstin; Weichert, Wilko; Altmann, Gabriela; Roth, Claudia; Winzer, Klaus-Jürgen; Kristiansen, Glen; Petry, Christoph; et al. (Diagnostic molecular pathology, 2011)
formalin-fixed paraffin-embedded (FFPE) tissue. The aim was to show that this approach is feasible and gives results that are comparable to the current gold standards. Expression of the breast cancer biomarkers ESR1, PGR, and HER2 was measured in a total of 501 FFPE tissue samples from 167 breast carcinomas, which had been stored for up to 21 years. Total RNA was extracted from tissue sections and biomarker expression was measured by kinetic RT-PCR (RT-kPCR). The results of the new method were compared with immunohistochemistry as the current gold standard. - - RNA was successfully isolated from all samples, with a mean yield of 1.4 μg/sample and fragment lengths of at least 150 bp in 99% of samples. RT-kPCR analysis of ESR1, PGR, and HER2 was possible in all samples. Comparing RT-kPCR results with standard IHC, we found a good concordance for ESR1 (agreement: 98.4%), PGR (84.4%), and HER2 (89.8%). We observed a low section-to-section variability of kPCR results for all 3 biomarkers (root of mean squared errors: 0.2 to 0.5 Ct values). The new approach is a reliable high-throughput instrument for standardized testing of biomarkers in clinical routine and for research studies on archived FFPE material up to 21 years old. For the assessment of ESR1, PGR, and HER2 the results are comparable to the current gold-standard....
Gesehen am 14.09.2022